The Impact of the Constitutional Court's Decision on the Revocation of Authority of the Prosecutor submits a Judicial Review - Yunus, Nur Rohim; Suhendar, Suhendar; Rezki, Annissa (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2023)
The right to justice, and human rights more generally, requires the filing of a judicial review (PK) in Indonesia. A judicial review (PK) can be requested by an individual who believes that his rights have been infringed or that the court's judgment is incorrect. The cassation decision can be challenged in court by either the convicted person or the prosecution if they believe it violates basic principles of fairness and legal certainty. However, the Constitutional Court can in its decision revoke the prosecutor's authority to submit a judicial review (PK) because it is considered contrary to human rights, especially in terms of recognition, guarantees, protection and fair legal certainty and equal treatment before the law. This study used a qualitative research method with a statutory and literature approach. The results of the study stated that it was very important for the prosecutor to have the right to submit a judicial review (PK) on the cassation decision of the Supreme Court which was deemed not to have fulfilled legal certainty and justice for the victim and the state. If this is omitted, it will cripple law enforcement. The reason for submission, guarantee, protection and legal certainty for the convict cannot be fully recognized, because there are still rights to guarantee, protection and legal certainty for the victim and the people of Indonesia which must also be maintained and respected.